937. Virally Suppressed PLH Switching From Abacavir to Tenofovir Alafenamide Did Not Have Changes in Immune Activation or Inflammation. (26th November 2018) - Funderburg, Nicholas; Mccomsey, Grace; Kulkarni, Manjusha; Bowman, Emily R; Gabriel, Janelle; Snyder, Brandon; Mallon, Patrick; Winston, Alan; Sengupta, Devi; Yan, Mingjin; Rhee, Martin S; Das, Moupali
Abstract: Background: Abacavir (ABC) use has been associated with increased risk of myocardial infarction in persons living with HIV (PLH). Its mechanism is unknown, but may involve immune activation inflammation, and/or altered platelet reactivity. In the current analysis, we compared changes in biomarkers of immune activation and inflammation associated with increased cardiovascular (CV) mortality in virally suppressed PLH who switched off ABC to tenofovir alafenamide (TAF) to those who remained on ABC. Methods: In a randomized, double-blinded, active-controlled trial (GS US 311–1717), virally suppressed PLH on a stable regimen containing ABC plus lamivudine (3TC) were randomly assigned (1:1) to maintain therapy or to switch to TAF plus emtricitabine (FTC) while continuing their third agent. At baseline (BL) and weeks 4, 12, 24, and 48 plasma markers (IL-6, hsCRP, D-Dimer, sCD14, sCD163, TNF-R1, and TNF-R2) were measured by ELISA; Lp-PLA2 levels were measured by the Plac assay. Differences between treatment groups overtime were assessed by 2-sided Wilcoxon rank-sum tests. Results: Of 556 PLH randomized, 548 had samples available for biomarker assessments (TAF: 274; ABC: 274), both arms were of similar CD4 (median 671 cells/μL), age (median 52 years), race (73% white), but there were fewer women in the TAF arm (14% vs. 22%, P = 0.015) at baseline (BL). Mean BL ASCVD scores were 7.9 in both arms (>7.5 is increased CV risk). BL biomarker concentrations were similar between arms: most had high concentrations of Lp-PLA2 ≥200 ng/mL (94%) and one-third had elevated hsCRP levels >3 mg/L (34%). After switching from ABC to TAF, sCD14 had an early (W12) decreased (−3.4% vs. −0.1%, P = 0.023), while sCD163 increased at both W4 (2.5% vs. −1.2%, P = 0.02) and W24 (1.4% vs. −0.8%, P = 0.025) in the TAF arm; levels of sTNF-R1 also increased through W24 (3.2% vs. 0.2%, P = 0.003) (figure). There were no significant differences in percentage changes from BL between arms for levels of Lp-PLA2, hsCRP, IL-6, D-dimer, or TNF-R2. Conclusion: Prior to switching from ABC to TAF, virally suppressed PLH with mean ASCVD scores of 7.9 had elevated levels of CV risk markers (Lp-PLA2 and hsCRP). Switching off ABC to TAF was not associated with any meaningful change in markers of immune activation or inflammation, suggesting that the ABC-associated increased MI risk may involve an alternative etiology. Disclosures: G. Mccomsey, Merck: Consultant, Consulting fee. ViiV: Consultant, Consulting fee. Gilead: Consultant, Consulting fee. Astellas: Grant Investigator, Research grant. Roche: Grant Investigator, Research grant. P. Mallon, Gilead Sciences: Grant Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Grant recipient and Speaker honorarium. GSK Ireland: Grant Investigator and Scientific Advisor, Grant recipient. A. Winston, Gilead, ViiV Healthcare, BMS, Janssen and Merck: Consultant, Grant Investigator, Investigator and Speaker's Bureau, Educational grant, Grant recipient, Research grant and Speaker honorarium. D. Sengupta, Gilead Sciences: Employee and Shareholder, Salary and Stock. M. Yan, Gilead Sciences: Employee and Shareholder, Salary and Stock. M. S. Rhee, Gilead Sciences: Employee and Shareholder, Salary and Stock. M. Das, Gilead Sciences: Employee and Shareholder, Salary and Stock.